Multi-constraint Zigbee routing to prolong lifetime of mobile wireless sensor networks. (25th July 2019) - Kaliyar, Pallavi; Lal, Chhagan; Choudhary, C.M.; Sharma, Lokesh
Mobile wireless sensor network (MWSN) characteristics (i.e., dynamic topology, low bandwidth, and finite energy) cause a threat to MWSN's basic functionalities that includes network formation, self-organisation, route discovery, and communication management. Hence, improving the lifetime and minimising the mobility induced route breaks are the critical issues in MWSNs. In this paper, we propose a multi-constraint Zigbee based reactive routing (MZRR) protocol for MWSNs to extend their network lifetime. Our MZRR protocol uses node energy and hop-to-hop transmission efficiency along with network mobility as metrics during the route discovery phase. MZRR protocol ensures that the discovered routes have high transmission efficiency which leads to low energy and link bandwidth consumption in the network. By keeping the energy utilisation of sensors balanced, MZRR protocol avoids the dead zones in surveillance areas.We implement MZRR protocol on NS-3, and the results are compared with traditional ad-hoc on-demand distance vector and state-of-the-art routing algorithms.